A new approach to event-triggered static output feedback control of networked control systems. (November 2016) - Shen, Mouquan; Yan, Shen; Zhang, Guangming
Abstract: This paper is concerned with the event-triggered static output feedback control of networked control systems. The event-triggered mechanism is represented by a time-delay model and some latest techniques are employed to deal with the induced time-delay. Furthermore, a novel strategy is developed to eliminate the coupling among control gain, input matrix and output matrix. With these techniques, a new sufficient condition for system stability is established in the framework of linear matrix inequalities. The effectiveness of the proposed method is shown by two numerical examples. Abstract : Highlights: A delay approach is utilized to model the event-triggered mechanism. Some new techniques are employed to deal with the induced time-delay. Static output feedback controller gain is calculated by means of linear matrix inequalities. Some simulations are carried out to show the effectiveness of the proposed method.